Virulence factors of lactose-negative Escherichia coli strains isolated from children with diarrhea in Somalia. - Nicoletti, M (1988)
Lactose-negative Escherichia coli strains were isolated at high frequency from children with diarrhea in Somalia during a 2-year study on diarrheal diseases. Sixty-four of these strains, considered to be a representative sample, were characterized for virulence factors, plasmid profiles, and antibiotic resistance. Of these strains, 5 were recognized as enteroinvasive E. coli (they were serotyped as O135:K-:H-), 6 belonged to classical enteropathogenic E. coli serotypes, 9 were able to adhere to tissue culture cells (of these, 4 showed a pattern of localized adherence and 1 was an enteropathogenic strain), 18 were both adherent and hemolytic, and 8 were simply hemolytic. None hybridized with 32P-labeled heat-labile or heat-stable (a and b) enterotoxin gene probes or produced moderate or high-level cytotoxic effects on HeLa cells. Of the 64 strains examined, 24 produced mannose-resistant hemagglutination with human, chicken, and monkey erythrocytes. One of these was serotyped as O4:K-:H8, and a rabbit O antiserum raised against this strain allowed us to establish that 23 strains had the same O antigen. The 23 O4 strains were hemolytic and were not enterotoxic for rabbit ileal loops, and intact bacteria were able to destroy tissue culture cell monolayers very rapidly. The uniformity of the antibiotic resistance pattern and of the plasmid DNA content, together with the fact that they were isolated in different years and in different children, suggests that the O4 strains must be epidemiologically relevant in Somalia. A possible diarrheagenic role for the adherent-hemolytic E. coli strains is also discussed.